Applications of Artificial Intelligence in Electronics - Rekha (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Artificial Intelligence (AI) has significantly transformed various industries, including electronics, by enabling smarter systems, automating complex processes, and optimizing performance across a range of devices and applications. The integration of AI into electronic systems, from microchips and sensors to robotics and consumer electronics, has led to advancements in automation, data analysis, energy efficiency, and user experience. This paper explores the diverse applications of AI in electronics, focusing on areas such as circuit design, manufacturing, embedded systems, robotics, predictive maintenance, and consumer electronics. Additionally, the challenges of incorporating AI into electronics and the potential for future developments in this interdisciplinary field are discussed.